Siddur hatefillah : the Jewish prayer book : philosophy, poetry, and mystery - Schweid, Eliezer, 1929-2022 (Academic Studies Press, 2022)
Hebrew University Professor and Israel Prize recipient Emeritus Eliezer Schweid (1929-2022), widely recognized a one of the greatest historians of Jewish thought of our era, probes texts of the Jewish prayer book which process religious philosophical teaching into the language of prayer. With the addition of historical, philological, and literary contexts, the volume provides the reader with first-time access to the comprehensive meaning of prayer.